Enhanced interaction of L-selectin with the high endothelial venule ligand via selectively oxidized sialic acids. - Norgard, K E (1993)
The selectins are adhesion receptors that play key roles in leukocyte trafficking. Each has an N-terminal C-type lectin domain that binds to specific carbohydrates in a calcium-dependent manner. L-selectin recognizes sulfated, sialylated ligands on lymph node high endothelial venules. This recognition is abolished by strong periodate oxidation under conditions that destroy oligosaccharides. In contrast, mild periodate oxidation, which selectively oxidizes the side chain of sialic acid residues without affecting the underlying oligosaccharide, markedly enhances this interaction. The enhancement is calcium dependent, indicating that lectin recognition is maintained. Reduction of the sialic acid aldehydes generated by mild periodate to alcohol groups abolishes this effect. Covalent cross-linking of the oxidized ligand to L-selectin can be demonstrated, suggesting Schiff base formation between lysine residues of the selectin and the newly formed aldehydes. Such selectively oxidized sialylated ligands could be used to probe the lectin domains of the selectins and to identify lysine residues near the binding site. Also, this approach could be used to design drugs for disrupting leukocyte-endothelial interactions leading to pathological inflammation.